An analysis of populations of Tagosodes orizicolus (Muir) us a vector of rice hoja blanca virus in rice areas of Colombia - REYES, LUIS ANTONIO; YENCHO, CRAIG; VELASCO, CECILIA; CALVERT, LEE (Revista Colombiana de Entomología, 1997)
The incidence of the rice hoja blanca virus (RHBV) is increasing in Colombia. The ability to transmit the RHBV is a genetically controlled trait in the vector T orizicolus. Since in nature there are many factors that influence the percentage of E orizicolus that are vectors, this study was undertaken to determine the percentage of the insect with the genetic capability to transmit RHBV. In several rice-growing regions of Colombia, samples of T orizicolus were collected from fíelds that had different levels of RHBV infestation. The percentage of insects with the genetic capability to transmit RHBV was always higher than the percentage of insects that were viruliferous vectors in the field. This method is useful as an indicator and has helped identify the rice-growing regions in Colombia that are at greatest risk of epidemics of RHBV.